2003
DOI: 10.3346/jkms.2003.18.4.494
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Transcription Factor-1 (TTF-1) Expression in Human Lung Carcinomas: Its Prognostic Implication and Relationship with Expressions of p53 and Ki-67 Proteins

Abstract: This study was aimed to evaluate the prevalence and prognostic implication of thyroid transcription factor-1 (TTF-1) immunoreactivity in 81 human lung carcinomas, including 65 cases of non-small cell lung carcinoma (NSCLC) and 16 cases of small cell lung carcinoma (SCLC); and also to investigate its relationship with the cell proliferation and regulation by immunostaining of Ki-67 and p53 proteins, respectively. The immunohistochemical staining for TTF-1 (clone 8G7G3/1) was performed and several clinicopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
60
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 28 publications
4
60
1
1
Order By: Relevance
“…33,34 The prognostic value of TTF-1 was evaluated in non-small-cell carcinomas, and contradictory results were reported. 35,36 We found that TTF-1 was detectable in 33% of classic large cell carcinoma cases, 24% of large cell neuroendocrine carcinoma, and 57% in small cell carcinoma. TTF-1 had a poor prognostic implication in small cell carcinoma in our study.…”
Section: Discussionmentioning
confidence: 76%
“…33,34 The prognostic value of TTF-1 was evaluated in non-small-cell carcinomas, and contradictory results were reported. 35,36 We found that TTF-1 was detectable in 33% of classic large cell carcinoma cases, 24% of large cell neuroendocrine carcinoma, and 57% in small cell carcinoma. TTF-1 had a poor prognostic implication in small cell carcinoma in our study.…”
Section: Discussionmentioning
confidence: 76%
“…TTF-1 is generally expressed diffusely in thyroid tumors but TTF-1 immunoreactivity varies according to tumor type in lung tumors (6). The TTF-1 immunoreactivity rate in primary lung ACs has been reported to be 60% to 100% (6,(38)(39)(40)(41). Studies reporting a lower staining percentage have emphasized the reason as TTF-1 immunoreactivity being lower in mucinous ACs compared to nonmucinous cases (38)(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 92%
“…The TTF-1 immunoreactivity rate in primary lung ACs has been reported to be 60% to 100% (6,(38)(39)(40)(41). Studies reporting a lower staining percentage have emphasized the reason as TTF-1 immunoreactivity being lower in mucinous ACs compared to nonmucinous cases (38)(39)(40)(41)(42). TTF-1 is widely utilized in the identification of ACs of lung origin as TTF-1 has been determined to be negative in extra-pulmonary ACs other than some rare ovarian carcinomas (6,43).…”
Section: Discussionmentioning
confidence: 99%
“…A positive TTF1 staining has been inversely related to the proliferative activity evaluated through Ki-67 expression, usually considered as a marker of poor prognosis in NSCLC (Pelosi et al, 2001;Myong, 2003). On the other hand, a correlation between positive TTF1 staining and various molecular markers expression such as p53 or HER2/neu involved in lung carcinogenesis has been suggested (Haque et al, 2002;Yatabe et al, 2002;Myong, 2003). Thus, further biological investigations are needed.…”
Section: Discussionmentioning
confidence: 99%
“…A study on 222 stage I NSCLC patients demonstrated no survival difference associated with TTF1 immunoreactivity (Pelosi et al, 2001), while another study correlated a positive TTF1 staining of resected NSCLC with a poor survival (Puglisi et al, 1999). On the other hand, four studies on early stages of NSCLC associated a positive TTF1 staining with a longer survival (Haque et al, 2002;Myong, 2003;Tan et al, 2003;Saad et al, 2004). However, all these studies were interested in surgical NSCLC patients and all but one (Saad et al, 2004) included both ADC and non-ADC histological types of NSCLC.…”
mentioning
confidence: 99%